PENGARUH DISIPLIN KERJA TERHADAP KINERJA DENGAN MODERASI KEPEMIMPINAN KEPALA SEKOLAH DAN SUPERVISI (Studi pada Guru SD Negeri di UPTD Pendidikan Kecamatan Genuk Semarang - Dwi Utomo, Hery (Students Journal of Economic and Management, 2012)
This study aims to examine and analyze the role of leadership and supervision of work discipline moderating influence on the performance of elementary school teachers in the district UPTD Pendidikan Genuk Semarang with leadership and supervision as a moderating variable. The study population was 235 people, while the sample taken as 148 people for the study using the formula Slovin. Sampling using purposive sampling technique. Test instruments used are validity and reliability. Test requirements analysis using tests of normality and multicollinearity test. Test model used is the determinant coefficient and F-test (Goodness of Fit). Hypothesis testing use the t test. Based on the results of the study can be summarized as follows: (1) Work Discipline significant effect on teacher performance, (2) leadership significant effect on teacher performance, (3) supervision significant effect on teacher performance, (4) Leadership does not strengthen the influence of the work Discipline on teacher performance, (5) supervision strengthen the influence of the work Discipline on teacher performance. Key words: work discipline, leadership, supervision, teacher performance.